Posttraumatic growth from the perspective of narrative approach to the study of personality - Yatsenko, Viktoriia; Darvishov, Nariman (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. Today's challenges require a person to be able to cope with crises and integrate this experience for personal growth, which is reflected in such psychological phenomena as post-traumatic growth (PTG). Given the methodological limitations of previous quantitative studies of this problem, there was a need to expand the understanding of post-traumatic growth using new methodological approaches, in particular narrative methods. In this literature review, we set out to explore the sources in which the post-traumatic growth studied within the framework of the narrative theory of personality, and sought answers to the following questions: a) how can post-traumatic growth be reflected in the narratives of people who have experienced traumatic experiences?; b) how effective is psychotherapy using narrative techniques in facilitating PTG of post-traumatic growth?Results. An analysis of the existing literature showed that the study of post-traumatic growth within the framework of the theory of narrative identity remains a promising and understudied direction. The most adaptive themes through which post-traumatic growth can manifest itself in people's life stories are the themes of agency and redemption, which have been linked in a number of studies to deeper cognitive processing of memories, psychological maturity, prosocial personality traits, and improved mental health. The central process that determines the subjective interpretation of one's life history and the development of a narrative identity is the process of meaning-making. So far, there has been little research on the effectiveness of narrative techniques in facilitating post-traumatic growth.Conclusions. The limitations of this review and the prospects for further research are discussed, emphasizing the importance of studying the dynamics of post-traumatic growth at the level of narrative identity using longitudinal designs and mixed methodology. It also discusses the prospects for integrating existing and future research on this issue into the practice of psychotherapy.
Keywords: posttraumatic personality changes; psychological trauma; life story; narrative identity; psychotherapy